Eriophyoid mite fauna (Acari: Trombidiformes: Eriophyoidea) of Turkey: new species, new distribution reports and an updated catalogue - Denizhan, Evsel; Monfreda, Rosita; Lillo, Enrico De; Çobanoğlu, Sultan (Zootaxa, 2015)
More than one hundred species of Eriophyoidea have been recorded hitherto from Turkey. Within the last decade, a large plant survey was carried out in order to investigate the eriophyoid fauna present in Turkey, with particular emphasis on species affecting weeds and ornamental plants. In addition, the Turkish literature has been examined for previous records of eriophyoid mites. New species, Paraphytoptus intybi n. sp. on common cichory, Cichorium intybus (Compositae) and Phytoptus albae n. sp. on white poplar, Populus alba (Salicaceae), are described and illustrated herein. In addition, a further 31 species were found to be new records for the eriophyoid fauna of Turkey with Aceria calaceris, Phyllocoptes didelphis and Vasates immigrans being new reports for the Palaearctic region. All known eriophyoid species records from Turkey appearing in papers published up until March 2013 are listed in this catalogue along with remarks and information on their current distribution in Turkey and taxonomic status.